BANKING RISK ANALYSIS OF BANKING FINANCIAL PERFORMANCE (Empirical Study on LQ45 Registered Banking Period 2014 – 2019) - Eha Hasni Wahidhani (Bajang Institute, 2022)
Banking is one of the institutions that influence economic growth and becomes the only state financial intermediary, this causes the level of public confidence in depositing funds in the banking sector is very high. High public confidence in depositing funds in banks is also an influence and value for financial performance in banks. This banking risk can be minimized if the bank can manage and control the risk properly. Therefore from the beginning the bank must be able to identify problems or risks to come. Not only the banks should be able to identify future risks, the debtor should also be able to identify the risks to a bank by analyzing its financial statements to find out how high the level of health and performance at the bank. To find out how well a bank performs can be seen from profitability